Exploring the Power of Hide-and-Seek: A Promising Approach to Foster Social Skills Development in Children at TK Al-Fadlilah Yogyakarta - Soniyatul Ummah, Evi; Sofarina, Dwi Amelia (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2023)
This scientific article investigates the potential of the game